Effect of acid-digested rice straw waste feeding methods on the 3HV fraction of bacterial poly(3-hydroxybutyrate-co-3-hydroxyvalerate) production. Issue 12 (December 2016) - Ahn, Junmo; Jho, Eun Hea; Nam, Kyoungphile
Graphical abstract: Highlights: Rice straw hydrolysate contains multiple carbon sources including inhibiting ones. Inhibitory effects can be reduced by diluting the hydrolysate. H/M ratio of 2:8 was appropriate for P(3HB-co-3HV) synthesis from the hydrolysate. The PHAs contents could be increased by using the split-fed method. The desired 3HV fraction can be obtained by using the repeatedly-fed method. Abstract: The effect of different feeding methods of the acid-digested rice straw hydrolysate on the contents and composition of polyhydroxyalkanoates (PHAs) accumulated by Cupriavidus necator was studied. The results showed that the inhibitory effects of furanic compounds on bacterial PHAs synthesis can be alleviated by dilution, and the hydrolysate-to-media (H/M) ratio of 2:8 was appropriate for poly-3-hydroxybutyrate-co-3-hydroxyvalerate [P(3HB-co-3HV)] synthesis. At the H/M ratio of 2:8, the accumulated PHAs content could be increased by using the split-fed method, and the rice straw hydrolysate fed in 4-pulses resulted in the highest P(3HB-co-3HV) concentration in this study. However, the 3-hydroxyvalerate (3HV) mol% decreased with increasing PHAs concentration, thus, the repeatedly-fed method was used to achieve a desirable 3HV fraction range of 20–30% for medical applications. The repeated feeding of the hydrolysate increased the 3HV fraction of the accumulated P(3HB-co-3HV) to the 20–30% range. Overall, this study demonstrates that the feeding methods of rice straw hydrolysates containing multiple carbon sources can be optimized for synthesis of desired PHAs.